Do Natives' Beliefs About Refugees' Education Level Affect Attitudes Toward Refugees? Evidence from Randomized Survey Experiments - Philipp Lergetporer; Marc Piopiunik; Lisa Simon (Center for Economic Studies and ifo Institute (CESifo), 2017)
In recent years, Europe has experienced an unprecedented influx of refugees. While natives' attitudes toward refugees are decisive for the political feasibility of asylum policies, little is known about how these attitudes are shaped by refugees' characteristics. We conducted survey experiments with more than 5,000 university students in Germany in which we exogenously shifted participants' beliefs about refugees' education level through information provision. Consistent with economic theory, we find that beliefs about refugees' education significantly affect concerns about labor market competition. These concerns, however, do not translate into general attitudes because economic aspects are rather unimportant for forming attitudes toward refugees.
Keywords: H12; H53; I38; D83; D72; P16; 330; refugees; information provision; education; survey experiment; labor market